Analisis Pengungkapan Lingkungan Berdasarkan Global Reporting Initiatives (Gri) G4 - Doni Syahputra; Herlina Helmy; Erly Mulyani (Universitas Negeri Padang, 2019)
This study aims to analyze: 1) The level of environmental disclosure of PT Bukit Asam (Persero), Tbk. and PT Indo Tambangraya Megah, T;bk. for the year 2016-2017 based on the GRI G4 Guideliness, 2) The breadth and depth of environmental disclosure of PT Bukit Asam (Persero), Tbk. and PT Indo Tambangraya Megah, Tbk. for the year 2016-2017. This is a descriptive qualitative research using two mining companies, namely, PT Bukit Asam (Persero), Tbk. and PT Indo Tambangraya Megah, Tbk. Data for this study were secondary from annual report and sustainability report were analysed using content analysis technique. The results show that: 1) the level of disclosure on economic, social and environmental performance indicators is higher for PT Aneka Tambang, Tbk. compared to those of PT Vale Indonesia, Tbk. 2) the breadth and depth of sustainability report disclosure of PT Indo Tambangraya Megah, Tbk, is better compared to those of PT Bukit Asam (Persero), Tbk.